OPTIMIZATION OF LSTM HYPERPARAMETERS USING GREY WOLF OPTIMIZATION AND HYPERBAND FOR PREDICTING BRI STOCK PRICES - Eko Budi Pratama; Rudi Nurdiansyah; Muhammad Ali Ridho; Irsyad Khoirun Ramadhan; Ibnu Toharri (RADJA PUBLIKA, 2026)
This research compares the performance of the Hyperband and Grey Wolf Optimization (GWO) algorithms in optimizing the hyperparameters of the Long Short-Term Memory (LSTM) model for predicting the stock price of Bank Rakyat Indonesia (BRI). Stock price prediction is a complex problem due to the dynamic and nonlinear characteristics of time series data. The dataset used consists of historical BRI stock data for the 2018-2025 period, obtained from Yahoo Finance. The optimization process was performed on several LSTM hyperparameters, including units, learning rate, dropout, optimizer, batch size, and epoch. Model performance was evaluated using Root Mean Square Error (RMSE). The results show that the LSTM-GWO model outperforms the LSTM-Hyperband model, with an RMSE of 75.93 compared to 77.60. However, Hyperband is more computationally efficient than GWO. The findings indicate that the GWO algorithm is more effective at improving prediction accuracy, while Hyperband excels in tuning efficiency. This study is expected to contribute to the development of hyperparameter optimization methods for deep learning models used in time-series-based stock price prediction.